A IDENTIFIKASI JENIS DAN KELIMPAHAN GASTROPODA DI PANTAI TELUK SEPANG KOTA BENGKULU - Rizki Slamet; Dewi Purnama; Bertoka Fajar SP Negara (Jurnal Perikanan Unram, 2021)
Gastropods are snails that have high economic value because their shells are used for jewelry and souvenirs, while the meat is a delicious food. Several types of snails that have economic value include the families Strombidae, Cypraeidae, Olividae, Conidae, and Tonnidae. Studying the importance of the benefits of Gastropods, it is necessary to study these animals. Therefore, researchers are interested in conducting research on Gastropod animals which include the types and abundance of gastropods in the waters of Bengkulu City, especially in the Sepang Bay Beach, Bengkulu City. This study used a survey method using a 1x1 meter transect. The measured data are in the form of abundance data and Gastropod data. Based on the research results, there are nine types of Gastropods with an abundance of 216 ind /m2 Cerithidea cingulata, 7 ind / m² Natica gualteriana, 3 ind/m² Trochusconus, 8 ind / m2 Turbo chrysostomus, 7 ind / m2 Telescopium telescopium, 9 ind / m2 Strombus labiatus, 162 ind / m2 Cerithidea blunt, 3 ind / m2 Vexillum rugosum, and 164 ind / m2 Cerithide aquadrata. Key words: Gastropods, Teluk Sepang beach, identification, Molluscs